Characterisation of Drug-Related Problems and Associated Factors at a Clinical Pharmacist Service-Naïve Hospital in Northern Sweden - Peterson, Cecilia (Drugs Real World Outcomes, 2017)
BACKGROUND: Polypharmacy and increased sensitivity to side effects cause adverse drug events, drug–drug interactions and medication errors in the elderly. OBJECTIVE: The objective of this study was to investigate the prevalence and type of drug-related problems and associated factors among patients admitted to a clinical pharmacist service-naïve medical ward in an inland hospital in northern Sweden. METHODS: During September–November 2015 and February–April 2016, clinical pharmacists working as part of a ward team on the medical ward conducted 103 medication reviews. Drug-related problems were identified and classified. Associated factors, drug classes and specific drugs involved were also investigated. RESULTS: The clinical pharmacists identified 133 drug-related problems in 66% [68/103] of the study population. The most common drug-related problems in this study were inappropriate drug use and interactions. Cardiovascular drugs and psychotropic drugs were most commonly involved. Drug-related problems were more frequently observed at higher age, increasing number of drugs prescribed and in patients with reduced renal function. In the multivariate analysis, only the number of prescribed drugs was still significant. CONCLUSION: Drug-related problems were commonly observed among patients admitted to the medical ward. Medication reviews conducted by clinical pharmacists as part of a ward team resulted in several interventions to improve the patients’ drug treatment.